Cumulative Betel Quid Chewing and the Risk of Significant Liver Fibrosis in Subjects With and Without Metabolic Syndrome - Chou, Yu-Tsung; Sun, Zih-Jie; Shen, Wei-Chen; Yang, Yi-Ching; Lu, Feng-Hwa; Chang, Chih-Jen; Li, Chung-Yi; Wu, Jin-Shang (Frontiers in Nutrition, 2022)
Background: Betel quid chewing is associated with metabolic disorders, oral cancer, cardiovascular disease, and chronic liver diseases. Metabolic syndrome (MetS) is also a factor associated with liver fibrosis, cirrhosis, and HCC. However, studies on the relationship between betel quid and liver fibrosis while also considering MetS are lacking. The aim of this study was thus to investigate the association of betel quid chewing and liver fibrosis with MetS. Method: A total of 9,221 subjects were enrolled after excluding subjects < 18 years of age, with past history of chronic liver diseases, cancer, significant alcohol consumption, and incomplete data. Betel nut chewing habit was classified into three groups: none, former-chewing, and current-chewing, and cumulative exposure was calculated by multiplying the duration with the quantity. Liver fibrosis was evaluated based on the NAFLD fibrosis score (NFS), which is a composite score of age, hyperglycemia, BMI, platelet count, albumin, and the AST/ALT ratio. Significant liver fibrosis was defined as NFS ≥ -1.455. Result: After adjusting for other variables, MetS was positively associated with significant liver fibrosis. Subjects with both MetS and betel quid chewing had a higher associated risk of significant liver fibrosis than those with neither MetS nor betel quid chewing (adjusted OR: 3.03, 95% CI: 2.04-4.50, p < 0.001). Betel quid chewing was associated with significant liver fibrosis (adjusted OR:2.00, 95% CI: 1.14-3.49, p = 0.015) in subjects with MetS, but not in subjects without. Conclusion: MetS increased the associated risk of significant liver fibrosis. Cumulative betel quid exposure increased the associated risk of significant liver fibrosis in subjects with MetS, but not in subjects without.